The Processes of Building Panel Residential Buildings in the Cities of Uzbekistan (On the Example of Fergana) (Journal of Architectural Design, 2023)
In the article, on the example of the city of Fergana, the construction processes of cheap and high-quality residential houses in the cities of Uzbekistan were analyzed. Also, the differentiation of medium-sized and multi-storey residential buildings by series was shown